Risk Factors for Early Dialysis Dependency in Autosomal Recessive Polycystic Kidney Disease - GÖKCE, İBRAHİM (MOSBY-ELSEVIER, 2018)
Objective To identify prenatal, perinatal, and postnatal risk factors for dialysis within the first year of life in children with autosomal recessive polycystic kidney disease (ARPKD) as a basis for parental counseling after prenatal and perinatal diagnosis. Study design A dataset comprising 385 patients from the ARegPKD international registry study was analyzed for potential risk markers for dialysis during the first year of life. Results Thirty-six out of 385 children (9.4%) commenced dialysis in the first year of life. According to multivariable Cox regression analysis, the presence of oligohydramnios or anhydramnios, prenatal kidney enlargement, a low Apgar score, and the need for postnatal breathing support were independently associated with an increased hazard ratio for requiring dialysis within the first year of life. The increased risk associated with Apgar score and perinatal assisted breathing was time-dependent and vanished after 5 and 8 months of life, respectively. The predicted probabilities for early dialysis varied from 1.5% (95% CI, 0.5%-4.1%) for patients with ARPKD with no prenatal sonographic abnormalities to 32.3% (95% CI, 22.2%-44.5%) in cases of documented oligohydramnios or anhydramnios, renal cysts, and enlarged kidneys. Conclusions This study, which identified risk factors associated with onset of dialysis in ARPKD in the first year of life. may be helpful in prenatal parental counseling in cases of suspected ARPKD.
Keywords: GENOTYPE-PHENOTYPE CORRELATIONS; PKHD1 MUTATIONS; CLINICAL-EXPERIENCE; ARPKD; PROTEIN; ENCODES; GENETICS